Factors influencing accounting candidates preferences in Malaysia's higher learning institution / Maheran Zakaria and Wan Noraswaniaty Wan Ahmad - Zakaria, Maheran; Wan Ahmad, Wan Noraswaniaty (2021)
The shortage of chartered accountant in the accounting profession is currently considered a worldwide issue including Malaysia. Interested in this matter and following variables as proposed by Theory of Reasoned Action, the study aims to examine the factors affecting the intention of students in choosing accounting as their program preferences in relation to attitude and subjective norms among accounting students from a public higher learning institution in Malaysia. A total of 350 accounting students took part in this study. The study uses Smart Partial Least Square (PLS) version 3.0 to measure the research model. Findings exhibited that the variables namely attitude and subjective norms influenced student's intention to choose an accounting program. Additionally, the expectations of social groups were reasons where students were more likely motivated to comply. These results provided useful perspectives for corporate leaders, accounting professional associations, and university fraternities to establish policies by highlighting the importance, benefits, and opportunities of the accounting profession to students and social groups. The amassed efforts of the entire accounting fraternities will help to generate a strong interest in new talents in the field and ensure that more will come into the profession. It is expected that the initiative will create to produce a desired number of accountants in the future and therefore accelerates the desire of nations in becoming fully developed countries